Detection of carbapenem resistance mechanisms among Avian Pathogenic Escherichia coli (APEC) isolated from broiler chickens - El- shaer, Aya; Awad, Amal; Younis, Gamal (Journal of Veterinary Healthcare, 2023)
Background The emergence and spread of carbapenem-resistant gram-negative bacteria pose a serious threat to human health. Currently, little is known about the molecular mechanisms underlying carbapenem -resistance and their prevalence among APEC in Egypt. The aim of this study was to detect APEC in clinically diseased broiler chickens collected from broilers farms located at Dakahalia governorates, asses their virulence –associated genes, detect the antimicrobial susceptibility of recovered isolates and to detect genes encoding carbapenemase resistant. Methods A total of 100 organ tissue samples subjected to conventional culture technique for isolation of E. coli. The confirmed E. coli were subjected to disc diffusion method for detection their susceptibility to antimicrobials. Polymerase chain reaction (PCR) was used for detection of APEC virulence genes (hlyA, iutA, ompT, iss, iroN) and six carbapenem- resistant genes namely, blaIMP, blaVIM, blaKPC, blaOXA-48 blaGES and blaNDM,. Results Forty isolates were confirmed to be E. coli  among them, three or more APEC virulence- genes were detected from all isolates. The hlyA gene was detected in 90% (36/40), iroN in 95% (38/40), ompT in 97.5% (39/40), iutA in 92.5% (35/40) and iss was detected in 95% (38/40) of APEC isolates The tested isolates exhibited a remarkable resistance to ampicillin (97.5%), cefuroxime (92.5%), clindamycin (90%), chloramphenicol (62.5%), doxycycline (45%), amikacin (25%) and ciprofloxacin (12.5%). While, the retrieved isolates displayed 100 % sensitivity against imipenem, meropenem, ertapenem, ceftazidime and colistin. Concerning carbapenemase-encoding genes, blaIMP, blaVIM, blaKPC, blaOXA-48, blaGES  couldn’t be detected among the E. coli isolates, while, blaNDM was confirmed in three isolates . Conclusion The detection of NDM as one of the carbapenem resistant genes reveals that the resistant strains are not only capable of infecting humans, but that carbapenams- resistant E. coli (CREC)  has also started to pose a threat to poultry farm and other livestock animals. This may give rise to worries that these food-carrying creatures could infect humans or colonize them.
Keywords: APEC; carbapenemase-encoding genes; virulence-associated genes broiler chicken; antimicrobial susceptibility.